Pelatihan Penggunaan Media Sempoa Aritmatika Untuk Meningkatkan Kemampuan Berhitung Siswa SD - Mahsup, Mahsup; Sirajudin, Sirajudin; Palahuddin, Palahuddin; Sukuryadi, Sukuryadi (Universitas Muhammadiyah Mataram, 2025)
Abstract: This community service activity aims to improve the understanding of using arithmetic abacus media in elementary students' mathematics calculations. The implementation method of the activity consists of preparation, socialization, activity execution, and evaluation. The results of the activity show that the use of arithmetic abacus media is proven to be effective in enhancing elementary students' calculation abilities. This activity successfully had a positive impact on students' cognitive abilities and learning motivation. Students have an increased understanding, and the abacus media is effectively used in mathematics learning, which can enrich students' learning experiences.Abstrak: Kegiatan pengabdian ini bertujuan untuk meningkatkan pemahaman penggunaan media sempoa aritmatika dalam berhitung matematika siswa SD. Metode pelaksanaan kegiatan terdiri dari persiapan, sosialisasi, pelaksanaan kegiatan dan evaluasi. Hasil kegiatan bahwa penggunaan media sempoa aritmatika terbukti efektif dalam meningkatkan kemampuan berhitung siswa SD. kegiatan ini berhasil memberikan dampak positif terhadap kemampuan kognitif dan motivasi belajar siswa. Siswa memiliki pemahaman yang meningkat dan media sempoa efektif digunakan dalam pembelajaran matematika yang dapat memperkaya pengalaman belajar siswa.